EXPERIENCE OF REMOTE OBSTETRIC CENTERS IN THE KEMEROVO REGION IN THE CONTEXT OF A NEW CORONAVIRUS INFECTION - Елгина, Светлана Ивановна; Ушакова, Ирина Анатольевна; Рудаева, Елена Владимировна; Шибельгут, Нонна Марковна; Мозес, Вадим Гельевич (Medicine in Kuzbass, 2020)
Aim – to determine the effectiveness of dynamic monitoring and routing of pregnant women, women in labor and maternity hospitals in the context of the spread of a new coronavirus infection in obstetric remote consultation centers. Materials and methods. The course of pregnancy and childbirth, as well as the health status of newborns, were retrospectively studied in 24 women with COVID-19 who were in repurposed infectious diseases hospitals in Kemerovo. Routing of pregnant and maternity women in the Kemerovo region was carried out in accordance with the order of the Ministry of health of Kuzbass N 933 dated 17.04.2020 «On temporary routing of pregnant women, women in labor and women within 42 days after the end of pregnancy of any term and localization with SARS, community-acquired pneumonia, suspected new coronavirus infection COVID-19, patients with new coronavirus infection COVID-19». Results. Of the 24 pregnant women with COVID-19 – five were delivered. In three cases, the pregnancy ended with a caesarean section, and two had independent deliveries without complications. One patient was delivered for a reason directly related to coronavirus infection, four – for obstetric indications. In all cases, delivery was performed as standard without any special features. All deliveries were singleton, of which four newborns were full – term and one was premature. After testing for COVID-19 in newborns, negative results were obtained. All pregnant women, maternity patients and children were discharged with recovery. There are no dead. To date, 23 out of 24 obstetric patients have recovered. One pregnant woman with a mild course of the disease continues treatment in an infectious disease’s hospital. Conclusion. Routing of obstetric patients with COVID-19, carried out in accordance with the current order of the Ministry of Health of Kuzbass, allowed to avoid problems during hospitalization and subsequent delivery. Obstetric remote consultation centers play a priority role in implementing dynamic monitoring and routing of pregnant women, women in labor and maternity hospitals in the context of the spread of a new coronavirus infection.